The coordination of controlled foreign company legislation and international business taxation in developing economies with specific reference to South Africa - Lambrechts, Hendrik Frederik Johannes (University of Johannesburg, 2016)
This research is aimed at making out a case for the taxation of foreign source income in countries with developing economies. To this end the argument is presented that it is possible to tax foreign source income in a way that optimally coordinates the revenue entitlements of countries with developing economies, with the entitlement of multinational enterprises operating within their area of jurisdiction, to maximum profitability. It is proposed that this result may be achieved through the careful coordination of controlled foreign company (CFC) legislation and international business taxation in domestic law. To support this proposition, the following issues are addressed: a theoretical and conceptual framework for the implementation of a regime of foreign source income taxation in a country with a developing economy; an evaluation of the efficacy of the CFC legislation implemented in South Africa from which lessons in relation to the implementation of foreign source income taxation regimes in other developing countries are distilled; how the coordination of the interaction between a CFC regime, a domestic business income taxation regime, and an international business income taxation regime is effected; and an exposition of the factors that should be taken into account in the drafting of CFC legislation. To illustrate the possible real-world realisation of the coordination between CFC legislation and international business taxation in a country with a developing economy, model CFC provisions are drafted followed by an explanatory note on these provisions.
Keywords: Controlled foreign corporations; Double taxation; Foreign Corporations; International economic relations; South Africa; Taxation